Strategi Perlindungan Perempuan Korban Kekerasan dalam Rumah Tangga: Studi Kasus Dinas P2KBP3A Kabupaten Kediri - Khairunnisa; Ahmad Badi’ (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
Domestic violence (DV) is a violation of human rights that has serious impacts on the safety, well-being, and dignity of women. This study aims to describe the protection strategies implemented by the Office of Population Control, Family Planning, Women’s Empowerment, and Child Protection (DP2KBP3A) of Kediri Regency in safeguarding women victims of domestic violence, as well as to identify the supporting and inhibiting factors in their implementation. The research employed a qualitative method with a case study approach, involving interviews, observation, and documentation. Data analysis used the Miles and Huberman model, which consists of data reduction, data display, and verification. The findings indicate three main strategies: preventive (socialization and education), curative (complaint and counseling services), and rehabilitative (psychological recovery). Supporting factors include the commitment of the local government, service innovations, cross-sectoral collaboration, and the availability of psychological counseling. Meanwhile, inhibiting factors consist of limited budget, shortage of human resources, absence of a permanent safe house, and low public awareness. This study underscores the importance of comprehensive strategies in protecting women victims of domestic violence, supported by stronger regulations and more optimal implementation.